VALIDASI KECEPATAN ARUS SIMULASI NUMERIK MIKE 21 DENGAN KECEPATAN ARUS LAPANGAN PADA BANGUNAN GROIN PT. BODDIA GALESONG JAYA - Suyanto, Muhammad Cesar Wiratama; Fauzan, Dzaky (Departemen Teknik Kelautan Fakultas Teknik Universitas Hasanuddin, 2024)
Ocean currents are the flow of water in the ocean, influenced by factors such as temperature and salinity gradients, wind stress, gravitational forces from the moon, and bathimetry of ocean. These currents follow specific patterns and significantly impact climate, weather, and marine ecosystems. This study focuses on validating field measurements of current speed against simulated speed generated by the MIKE 21 software, a widely used tool for hydrodynamic modeling in coastal engineering. The validation process involved comparing in-situ measurements of current speed, obtained using an acoustic Doppler current profiler, with the simulated currents from MIKE 21. The simulation parameters were calibrated to reflect the field conditions accurately. The results indicated that the maximum discrepancy between field measurements and the model's simulated currents was approximately 6.3%. This level of agreement confirms that the MIKE 21 model accurately represents the field conditions. Therefore, the model's predictions can be reliably used for other hydrodynamic simulations and coastal management applications.